(untitled) (Iranian Journal of Kidney Diseases, 2013)
Urinalysis is a mandatory diagnostic tool for the evaluation of patients with kidney diseases. A workshop on urinalysis was held for nephrologists in Isfahan, Iran, on October 11-12, 2012. After the presentation of the results of a survey of the nephrology centers of Iran on urine microscopy, the most important aspects of urinalysis were presented and discussed. These included the following: (1) urinalysis by dipstick, which provides results in a few seconds, is simple to use, has a low cost, and is used worldwide for screening purposes, in spite of some limitations; (2) measurement of proteinuria by 24-hour urine collection, which still represents the reference method in spite of limitations due to frequent over or under collection errors; (3) protein-creatinine ratio in a random urine sample, which is recommended by international guidelines as an alternative to the measurement of 24-hour protein excretion; (4) microalbuminuria, which is seen as a marker of systemic endothelial damage; and (5) the urinary sediment, which is underused even among nephrologists in spite of the relevant diagnostic information it can supply in a wide spectrum of kidney diseases.